Detection of A/B toxin and isolation of Clostridium difficile and Clostridium perfringens from foals - Silva, R. O. S.; Ribeiro, M. G. [UNESP]; Palhares, M. S.; Borges, A. S. [UNESP]; Maranhao, R. P. A.; Silva, M. X.; Lucas, T. M. [UNESP]; Olivo, G. [UNESP]; Lobato, F. C. F. (Wiley-Blackwell, 2013)
Reasons for performing the studyToxin detection and screening could contribute to knowledge of the transmission patterns, risk factors and epidemiology of Clostridium difficile and Clostridiumperfringens.ObjectiveTo isolate C.difficile and C.perfringens and to detect A/B toxins in faecal samples from diarrhoeic and nondiarrhoeic foals.Study designCross-sectional observational study.MethodsA total of 153 samples from foals were collected: 139 samples from farms and 14 samples from diarrhoeic foals admitted to a veterinary hospital. The A/B toxins were detected by cytotoxicity assay. All suspected colonies of C.perfringens were subjected to polymerase chain reaction for detection of the major toxin genes (, , epsilon and ) and for detection of 2-, NetB- and enterotoxin-encoding genes. Furthermore, C.difficile and C.perfringens isolates were evaluated for in vitro antimicrobial susceptibility.ResultsSeven of 153 (4.6%) samples, all from diarrhoeic foals, were positive for C.difficileA/B toxin. Of these, 5 of 14 (35.7%) were from hospitalised foals, and only 2 of 63 (3.2%) diarrhoeic foal samples were from farms (P = 0.002). Clostridiumperfringens was isolated from 31 (20.3%) foals, of which 21 of 76 (27.6%) were diarrhoeic and 10 of 76 (13.2%) were nondiarrhoeic, demonstrating a difference between these 2 groups (P = 0.045). Only 4 strains were positive for the 2-encoding gene (cpb2). All C.difficile and C.perfringens isolates were susceptible to metronidazole and vancomycin.ConclusionsThe present report highlights the need for laboratory diagnostics to differentiate C.difficile-associated infection in foals from other causes of diarrhoea to facilitate adequate antimicrobial therapy.Potential relevanceMore studies are needed to clarify the role of C.perfringens as a primary agent of diarrhoea in foals.
Keywords: horse; colitis; nosocomial diarrhoea; A; B toxins